2018
DOI: 10.2174/1389203719666180514150921
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin: Major Physiological Functions and Applications

Abstract: Lactoferrin (lactotransferrin; Lf) is an iron-binding glycoprotein and one of the most important bioactivators in milk and other external secretions. It has numerous biological roles, including the regulation of iron absorption and modulation of immune responses, and has anti-microbial, anti-viral, antioxidant, anti-cancer, and anti-inflammatory activities. Lf regulates the quantity of iron absorbed in the intestine via its role in iron transport and can also chelate iron, directly or indirectly. Notably, it h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
82
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 0 publications
0
82
0
1
Order By: Relevance
“…Its amino acid sequence relationships place it in the wider transferrin family (Baker and Baker, 2005). It is known that lactoferrin regulates the quantity of iron absorbed in the intestine via its role in iron transport, and it can chelate iron, directly or indirectly (Hao et al, 2019). Lactoferrin has been used as an adjuvant therapy for some intestinal diseases and is now used in nutraceutical supplemented infant formula and other food products (Hao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its amino acid sequence relationships place it in the wider transferrin family (Baker and Baker, 2005). It is known that lactoferrin regulates the quantity of iron absorbed in the intestine via its role in iron transport, and it can chelate iron, directly or indirectly (Hao et al, 2019). Lactoferrin has been used as an adjuvant therapy for some intestinal diseases and is now used in nutraceutical supplemented infant formula and other food products (Hao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that lactoferrin regulates the quantity of iron absorbed in the intestine via its role in iron transport, and it can chelate iron, directly or indirectly (Hao et al, 2019). Lactoferrin has been used as an adjuvant therapy for some intestinal diseases and is now used in nutraceutical supplemented infant formula and other food products (Hao et al, 2019). Lactoferrin also has other numerous biological roles, such as the modulation of immune responses and anti-microbial, anti-viral, antioxidant, anti-cancer, and anti-inflammatory activities (Hao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also improves the health status of Alzheimer's disease patients. [13][14][15] Glyco-macropeptide, a peptide of kappa-casein, exhibits antithrombotic and anti-bacterial potential. α-lactalbumin also reveals antitumoral, antiviral, and antistress perspectives.…”
Section: Anti-microbial Proteinsmentioning
confidence: 99%
“…Studies have explored the effect of bLF on iron absorption of infant and suggested that formula fortified with bLF could significantly increase hematocrit, serum ferritin (SF), and reticulocyte levels (11)(12)(13)(14)(15)(16). Our previous study (17) also indicated that formula fortified with 38 mg/100 g of bLF positively affected the hemoglobin (Hb) and iron status of infants who were previously exclusively breastfed and suggested that the effects of bLF fortification on iron metabolic homeostasis were mainly exerted through promoting total body iron E-mail: 263662086@qq.com content (TBIC) and iron absorption in intestine.…”
mentioning
confidence: 99%